2016
DOI: 10.31018/jans.v8i1.809
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of endophytic actinomycetes from Syzygium cumini and their antimicrobial activity against human pathogens

Abstract: Isolation of endophytic actinomycetes is an important step to screen antimicrobial compounds to curb the threat of drug-resistant strains of human pathogens. Out of the 50 endophytic actinomycetes obtained from surface sterilized root, stem and leaf tissues of Syzygium cumini, 50 isolates (30%) exhibited antimicrobial activity. Antistaphylococcal activity was displayed by most of the isolates, with maximum percent inhibition by J-10 (Mean of Inhibition Factor=12.12 mm2). A total of 8 isolates (4 each) were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
5
9
0
Order By: Relevance
“…The study explored that, leaves of A. tenuifolius are inhabited by actinomycetes. In this context, the results are in line with that achieved by Saini et al (2016), where out of the 50 endophytic isolates from different organs only one isolate yielded from leaf segment of Syzygium cumini. Similar trend was observed by other previous researchers, where Phuakjaiphaeo and Kunasakdakul (2015) reported that after 4 weeks of incubation at 30°C, only 4 out of 36 isolates of endophytic actinomycetes were obtained from leaf part of Centella asiatica.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The study explored that, leaves of A. tenuifolius are inhabited by actinomycetes. In this context, the results are in line with that achieved by Saini et al (2016), where out of the 50 endophytic isolates from different organs only one isolate yielded from leaf segment of Syzygium cumini. Similar trend was observed by other previous researchers, where Phuakjaiphaeo and Kunasakdakul (2015) reported that after 4 weeks of incubation at 30°C, only 4 out of 36 isolates of endophytic actinomycetes were obtained from leaf part of Centella asiatica.…”
Section: Discussionsupporting
confidence: 87%
“…Similar trend was observed by other previous researchers, where Phuakjaiphaeo and Kunasakdakul (2015) reported that after 4 weeks of incubation at 30°C, only 4 out of 36 isolates of endophytic actinomycetes were obtained from leaf part of Centella asiatica. According to Saini et al (2016), successful achievement of endophytic actinomycetes isolation from leaves of A. tenuifolius was strong evidence on success of the surface sterilization procedures. As he declared that, the epiphytic microbes are completely removed by 5% sodium hypochlorite, which is frequently used in plant surface sterilization procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low frequency of isolation (0.34%), compared with the isolation of terrestrial actinomycetes, was observed, in agreement with literature data (Passari et al, 2015 ). However, despite the lower isolation frequency a higher richness of genera was observed (Passari et al, 2015 ; Saini et al, 2016 ). We reported for the first time the isolation of strains close related to the species A. ponti (LGMB491) and Williamsia serinedens (LGMB479) as endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms such as bacteria and fungi can produce high quality metabolites on a large scale under optimized culture conditions [9]. This is because their metabolite production is reproducible, weather and season independent [10]. Microorganisms often produce metabolites that display distinctive molecular skeletons which are not even available in the chemical libraries [11].…”
Section: Introductionmentioning
confidence: 99%